Institutions, markets and men's and women's wage inequality: evidence from Ukraine - Ina Ganguli; Katherine Terrell (Institute for the Study of Labor (IZA), 2005)
Ukraine, the second largest country in the former Soviet bloc, is facing the challenge of rallying popular support for major structural reforms. As in most developing economies, the Orange Revolution government's success will depend on its ability to keep income distribution within an acceptable range. This paper is the first to make use of recent methodological developments in Lemieux's (2002) decomposition method to advance our understanding of the determinants of wage inequality in developing and transition economies. With an eye toward future policy, we apply this approach to the first large longitudinal micro data set for Ukraine
Keywords: C14; I2; J16; 330; the Ukrainian Longitudinal Monitoring Survey (ULMS); Lohndifferenzierung; Systemtransformation; Institutioneller Wandel; Ukraine; Geschlechterdiskriminierung